Efektivitas Pursed Lip Breathing Sebagai Mind-Body Therapy dalam Meningkatkan Pola Napas dan Menurunkan Kecemasan pada Pasien Asma Bronkial: Studi Kasus - Tentry Fuji Purwanti; M. Iqbal Sutisna; Kurniawati Kurniawati; Kartika Firdasari; Imawati Imawati; Listanty Widya Anggraeni; Rifki Permadi (Pusat Riset dan Inovasi Nasional, 2026)
Bronchial asthma is a chronic inflammatory disease of the respiratory tract characterized by recurrent episodes of dyspnea, wheezing, and coughing. Asthma management requires a comprehensive approach including pharmacological and non-pharmacological therapy. Pursed lip breathing as part of mind-body therapy can help improve breathing control and reduce anxiety in asthma patients. This case study aims to evaluate the effectiveness of pursed lip breathing application in improving breathing patterns and reducing anxiety levels in bronchial asthma patients. This research design is a descriptive case study of a 64-year-old female patient with bronchial asthma. Pursed lip breathing intervention was performed for 3 x 24 hours with evaluation of respiratory rate (RR), oxygen saturation (SpO₂), wheezing, anxiety level using Hamilton Anxiety Rating Scale (HARS), and sleep quality. Data were collected through physical assessment, observation, and interviews. After 3 days of intervention, there were significant improvements in all measured parameters. Respiratory rate decreased from 28 breaths/minute to 20 breaths/minute, oxygen saturation increased from 93% to 97%, wheezing disappeared, anxiety level decreased from moderate category (score 18) to mild (score 8), and sleep quality improved from 4-5 hours/night to 7-8 hours/night. The patient was able to perform pursed lip breathing technique independently on the third day. Pursed lip breathing is effective as an independent nursing intervention in improving breathing patterns and reducing anxiety in bronchial asthma patients. This technique can be integrated into holistic nursing care as part of asthma patient self-care management.